2017
DOI: 10.1002/asna.201713365
|View full text |Cite
|
Sign up to set email alerts
|

Radial velocity measurements and orbit determination of eight single‐lined spectroscopic binary systems

Abstract: Since early 2015, a new radial velocity monitoring campaign is going on at the University Observatory Jena. The aim of this project is to obtain current radial velocity measurements of selected single‐lined spectroscopic binary systems as well as to redetermine and/or constrain their orbital solutions. In this paper, we characterize the properties of the target sample of the project, describe the spectroscopic observations, data reduction, and analysis, and present the first results of the project, taken with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 14 publications
6
31
0
Order By: Relevance
“…The RVs of the measured telluric lines scatter on average on the 0.9 km s −1 level, which is consistent with the reached RV precision of the different observed targets. The long‐term RV stability of the spectrograph was already verified by Irrgang et al and Bischoff et al , and is also confirmed by our measurements, taken in the course of this project.…”
Section: Rv Measurementssupporting
confidence: 89%
See 1 more Smart Citation
“…The RVs of the measured telluric lines scatter on average on the 0.9 km s −1 level, which is consistent with the reached RV precision of the different observed targets. The long‐term RV stability of the spectrograph was already verified by Irrgang et al and Bischoff et al , and is also confirmed by our measurements, taken in the course of this project.…”
Section: Rv Measurementssupporting
confidence: 89%
“…Since 2013, the fiber‐linked Échelle spectrograph FLECHAS (Mugrauer et al ) is mounted on the 90‐cm reflector telescope while it is operated in the Nasmyth mode ( D = 90 cm, f / D = 15). As part of the Großschwabhausen binary survey (Mugrauer et al ), a radial velocity (RV) monitoring program was started in 2015 (Bischoff et al ) in order to redetermine, verify, improve, and constrain the Keplerian orbital solutions of spectroscopic binaries, selected from the ninth Catalogue of Spectroscopic Binary Orbits (SB9 hereafter, see Pourbaix et al ). The SB9 yields information about orbital elements of several thousand spectroscopic binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…This is the time when the L1 side of the primary is facing the line of sight, and it coincides with pulsation amplitude maximum, as we show below in Section 4. We find the best values for K and γ from the Bischoff et al (2017) RV data are unchanged from their values, 72.3 ± 0.3 and 0.7 ± 0.2 km s −1 , respectively.…”
Section: Co Cammentioning
confidence: 51%
“…The most recent radial velocity (RV) data on CO Cam were given by Bischoff et al (2017). We used the data from their Table A1 to reproduce the RV curve which we show here in Fig.…”
Section: Co Cammentioning
confidence: 99%
See 1 more Smart Citation